Topical capsaicin (low concentration) for chronic neuropathic pain in adults. - Derry, S; Moore, R (2012)
BACKGROUND: Topical creams with capsaicin are used to treat pain from a wide range of chronic conditions including neuropathic pain. Following application to the skin capsaicin causes enhanced sensitivity to noxious stimuli, followed by a period with reduced sensitivity and, after repeated applications, persistent desensitisation. There is uncertainty about the efficacy and tolerability of capsaicin for treating painful chronic neuropathies. This is an update of an earlier review of topical capsaicin for chronic neuropathic pain in adults that looked at all doses and formulations of capsaicin. The original review has now been split: here we consider only formulations using a low concentration of capsaicin (< 1%) applied several times daily over several weeks, while another review will consider a single application of capsaicin at a high concentration. OBJECTIVES: To review the evidence from controlled trials on the efficacy and tolerability of topically applied low-concentration (< 1%) capsaicin in chronic neuropathic pain in adults. SEARCH METHODS: Cochrane CENTRAL, MEDLINE, EMBASE and Oxford Pain Relief Database, searched to July 2012. SELECTION CRITERIA: Randomised, double-blind, placebo-controlled studies of at least six weeks' duration, using low-concentration (< 1%) topical capsaicin to treat neuropathic pain. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed study quality and validity, and extracted data. Information was extracted on numbers of participants with pain relief (clinical improvement) after at least six weeks, and with local skin reactions, and used to calculate relative risk (or risk ratio, RR) and numbers needed to treat to benefit (NNT) and harm (NNH). Details of definition of pain relief and specific adverse events were sought. MAIN RESULTS: No additional studies were identified for this update of low concentration capsaicin. Included studies were published before 1996. Six studies (389 participants in total) compared regular application of low dose (0.075%) capsaicin cream with placebo cream. There was substantial heterogeneity in results, probably as a result of the small number of studies each with small numbers of participants, as well as the different pain conditions studied and different definitions of "clinical success" reported. Only two studies reported data for the preferred primary outcome of at least 50% pain relief, and there were too few data for pooled analysis. Local skin reactions were more common with capsaicin, usually tolerable, and attenuated with time; the NNH for repeated low-dose application was 2.5 (95% confidence interval (CI) 2.1 to 3.1). All studies satisfied minimum criteria for quality and validity, but maintenance of blinding remains a potential problem. AUTHORS' CONCLUSIONS: There were insufficient data to draw any conclusions about the efficacy of low-concentration capsaicin cream in the treatment of neuropathic pain. The information we have suggests that low-concentration topical capsaicin is without meaningful effect beyond that found in placebo creams; given the potential for bias from small study size, this makes it unlikely that low-concentration topical capsaicin has any meaningful use in clinical practice. Local skin irritation, which was often mild and transient but may lead to withdrawal, was common. Systemic adverse effects were rare.